Violent Political Rhetoric, Generalized Imitation, Income Inequality, Gun Ownership, Changes in Gross Domestic Product, and Mass Shootings. Issue 47 (3rd September 2021) - Nugent, William R.; Conway, Anne
Abstract: Mass shootings represent a major public health crisis. There are economic, health, and mental health consequences of these events. A number of causes of mass shootings have been investigated. One cause that has been hypothesized but not yet investigated is violent political rhetoric (VPR). The current study used publicly available data to test for an association between VPR and mass shootings. Independent variables included income inequality, gun ownership, changes in gross domestic product, and a measure of VPR. Lagged values of the dependent variable tested for generalized imitation effects. Results of an analysis of a 54-year time series of mass shootings showed positive associations between mass shootings and VPR and income inequality. Results also showed a negative association between changes in gross domestic product and mass shootings. There was no evidence of a relationship between mass shootings and either gun ownership or generalized imitation. Implications of these results for future research, as well as for social workers and social services in health and mental health settings, are considered, including the creation and implementation of social services and programs designed to create empathy for targets of VPR and to reduce the use of VPR.